Biological assessment of fish assemblage environment in Garmat Ali River using Integrated Biological Index (IBI) during 2003 -2016 - Younis, Kadhim H.; Al-Thahaibawi, Basim M.; Al-Nagar , Ghassan A.; Al-Shamary, Ahmed (Mesopotamian Journal of Marine Sciences, 2024)
To provide a complete picture of the fish assemblage environment in this region, the present study used the Integrated Biological Index (IBI) to analyze the biological evaluation of the fish assemblage environment in the Garmat Ali River from 2003 to 2016. From the following primary groupings, seventeen units were used to construct the IBI (species richness, fish species composition, and trophic guilds). Forty-eight species were found overall, with 28 species found in the first period August 2003 to July 2004, 26 species discovered in the second period from November 2007 to October 2008, and 34 species found in the third period November 2015 - October 2016. The number of native species for each of the three time periods 14, 11, and 8, as well as the number of foreign species 5, 6, and 8, and marine migratory species 9, 9 ,and 18 for each of the three times. The percentage of native species for each of the three time periods was 60.5, 51.1, and 2.4%; the percentage of foreign species was 12.2, 34.5, and 69.7%; and the percentage of marine species for each of the three time periods was 27.5, 14.4, and 27.9%. For the three periods, the percentage of omnivore species individuals was 30.9, 31.08, and 80.6%, while the percentage of detrivore species individuals was 67.7, 45.6, and 2.2, For the three time periods, the percentage of individual carnivores was 1.4, 23.2, and 12.9%, whereas the percentage of individual herbivores was 0.2, 0 and 4.3%. The first period’s IBI value (61.8) was included under the Marginally impaired (60-80) category, and the second, and third periods’ values 59.3, and 53.9 respectively, were included under the Impaired category (below 60)